2022
DOI: 10.3390/pathogens11080919
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of the Central Variable Region in African Swine Fever Virus Isolates in the Russian Federation from 2013 to 2017

Abstract: African swine fever virus (ASFV), classified as genotype II, was introduced into Georgia in 2007, and from there, it spread quickly and extensively across the Caucasus to Russia, Europe and Asia. The molecular epidemiology and evolution of these isolates are predominantly investigated by means of phylogenetic analysis based on complete genome sequences. Since this is a costly and time-consuming endeavor, short genomic regions containing informative polymorphisms are pursued and utilized instead. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Even though the resolving power of this gene region in isolates from Africa ( 28 34 ) and the polymorphisms observed in isolates from Estonia ( 14 ), only two SNP-based CVR variants were detected in this study in wild boar viruses from Poland (CVR1-SNP2) and Lithuania (CVR1-SNP3). Recent studies describe the presence of additional CVR variants in isolates from Russia ( 35 ) and China ( 19 ) based on the presence of SNPs. However, the variants described in this study were unique and were not further identified in any of the ASFVs sequenced or available in the GenBank.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the resolving power of this gene region in isolates from Africa ( 28 34 ) and the polymorphisms observed in isolates from Estonia ( 14 ), only two SNP-based CVR variants were detected in this study in wild boar viruses from Poland (CVR1-SNP2) and Lithuania (CVR1-SNP3). Recent studies describe the presence of additional CVR variants in isolates from Russia ( 35 ) and China ( 19 ) based on the presence of SNPs. However, the variants described in this study were unique and were not further identified in any of the ASFVs sequenced or available in the GenBank.…”
Section: Discussionmentioning
confidence: 99%
“…The spread of ASFV across Europe and into Asia has been rapid, vast, and in the face of no effective vaccine, it will probably keep expanding its range into new countries globally [ 48 ]. While spreading across Eurasia, the clonal populations of the virus accrue mutations that can be common in a region and used for evaluating ASFV radiation events [ 24 , 30 , 41 ]. In this regard NGS promotes the generation of complete genome sequences and can be employed to track the virus from one outbreak to another, identifying innovative variants and assigning sequences to a specific variant group [ 14 , 26 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…These SNPs were synonymous (C/T) at position 480 and A/G at position 616. The latter SNP resulted in a threonine (T) exchange of alanine (A) at position 206 of the complete B602L predicted protein [ 24 ]. An alignment of the partial CVR ( B602L ) nucleotide sequence of different isolates indicating each of the six groups is depicted in Figure 2 .…”
Section: Essential Genetic Markers Used For Subtyping Genotype II Asfvsmentioning
confidence: 99%
“…The K145R, O174L, and MGF505-5R sequence analyses were performed in comparison with the Georgia 2007/1 reference sequence (GenBank accession number FR682468.2) [ 13 ]. For the B602L gene-sequence alignment, the representatives of the previously detected Estonian CVR variant strains (GenBank accession numbers MT647548 and MT647527) [ 7 ], Lithuanian LT14/1490 (GenBank accession number KJ627204) [ 2 ], and Russian CVR variant strains (GenBank accession numbers ON098036, ON098025, ON098023 and ON098019) [ 19 ] were added. For IGR I73R/I329L analysis, the index case of ASFV in the EU was included (GenBank accession MK628478) [ 20 ] to sequence alignment.…”
Section: Methodsmentioning
confidence: 99%